Aging and the aggregating proteome - David, Della C. (Frontiers in Genetics, 2012)
For all organisms promoting protein homeostasis is a high priority in order to optimize cellular functions and resources. However, there is accumulating evidence that aging leads to a collapse in protein homeostasis and widespread non-disease protein aggregation. This review examines these findings and discusses the potential causes and consequences of this physiological aggregation with age in particular in relation to disease protein aggregation and toxicity. Importantly, recent evidence points to unexpected differences in protein-quality-control and susceptibility to protein aggregation between neurons and other cell types. In addition, new insight into the cell-non-autonomous coordination of protein homeostasis by neurons will be presented.